Tinjauan Filosofis: Komparasi Pemikiran Maurice Bucaille dan Allama Tabatabai terhadap Sains dan Al-Qur’an - Bakti, Daud Kurniadi Yudistiro; Harahap, Syamil (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2023)
Abstract: The objective of this study is to philosophically and comparatively examine the perspectives of Maurice Bucaille and Allama Tabatabai on the relationship between Science and the Qur'an. The research employs an interpretative paradigm and utilizes the literature review. The data were obtained from research findings published in books and journals. The search parameters consist of the keywords Science, Al-Qur'an, Philosophy, Maurice Bucaille's Thought, and Allama Tabatabai. The results demonstrated that science acquires its veracity by employing empirical methodologies and objectively evaluating information. In Islamic teachings, science is inherently integrated with its principles. Bucaille unveiled that the Qur'an promotes the exploration of natural phenomena and their constituents as a means for humans to discern evidence of the omniscience of God through the application of their cognitive faculties. The proper exploration of nature and subsequent development of science and technology will be achieved through the application of systematic and focused thinking. Tabatabai stated that the most precise method to understand the concepts and goals of the Qur'an, as well as its connection with science, is by interpreting it using the Qur'an itself and drawing from the biographies of religious leaders who have provided interpretations. Abstrak: Penelitian bertujuan untuk mengalisis secara filosofis dan komparatif pandangan Maurice Bucaille dan Allama Tabatabai terhadap Sains dan Al Qur’an. Penelitian menggunakan paradigma interpretative dengan metode kepustakaan. Data dikumpulkan melalui hasil penelitian dalam bentuk buku dan jurnal. Adapun kata kunci yang menjadi parameter pencarian data adalah Sains, Al-Qur’an, Filosofi, Pemikiran Maurice Bucaille dan Allama Tabatabai. Hasil Penelitian menunjukkan Sains memperoleh kebenarannya melalui metode empiris, menilai informasi secara objektif. Dalam ajaran Islam, sains tidak dipisahkan dari prinsip-prinsipnya. Bucaille mengungkapkan ayat Al-Qur’an mendorong manusia mencari tanda-tanda kekuasaan Allah melalui perenungan atas fenomena alam beserta isinya dengan kekuatan akalnya. Dengan hasil pemikiran yang sistematis dan terarah, eksplorasi alam pun akan tercapai secara baik yang diikuti dengan perkembangan sains dan teknologi. Sementara Tabatabai menungkapkan tafsir Al-Qur'an dengan menggunakan Al-Qur'an sendiri, yang berasal dari biografi interpretatif para pemimpin agama, adalah cara yang paling akurat untuk mencapai konsep-konsep dan tujuan-tujuan Al-Qur'an termasuk hubungannya dengan ilmu pengetahuan.